2002
DOI: 10.1007/s10123-002-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial membrane injuries induced by lactacin F and nisin

Abstract: The combined action of nisin and lactacin F, two bacteriocins produced by lactic acid bacteria, is additive. In this report, the basis of this effect is examined. Channels formed by lactacin F were studied by experiments using planar lipid bilayers, and bactericidal effects were analyzed by flow cytometry. Lactacin F produced pores with a conductance of 1 ns in black lipid bilayers in 1 mM KCl at 10 mV at 20°C. Pore formation was strongly dependent on voltage. Although lactacin F formed pores at very low poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Although the molecule responsible for this effect was not purified and characterized by the authors, it could be lactacin F, a two-component class II bacteriocin produced by L. johnsonii and composed of LafA and LafX peptides which may combine to form a pore in the membrane of sensitive bacteria, resulting in the efflux of intracellular ions and the eventual death of the pathogen in this case. 31 As discussed later, the administration of this supernatant to adult patients colonized by H. pylori significantly decreased the values of 13 C-urea breath test ( 13 C-UBT). Similar findings were observed by Coconnier et al incubating H. pylori with the culture supernatant of L. acidophilus LB; the viability of the pathogen as well as its urease activity and its binding to the HT29-MTX cell line decreased in a dose-dependent manner.…”
mentioning
confidence: 84%
“…Although the molecule responsible for this effect was not purified and characterized by the authors, it could be lactacin F, a two-component class II bacteriocin produced by L. johnsonii and composed of LafA and LafX peptides which may combine to form a pore in the membrane of sensitive bacteria, resulting in the efflux of intracellular ions and the eventual death of the pathogen in this case. 31 As discussed later, the administration of this supernatant to adult patients colonized by H. pylori significantly decreased the values of 13 C-urea breath test ( 13 C-UBT). Similar findings were observed by Coconnier et al incubating H. pylori with the culture supernatant of L. acidophilus LB; the viability of the pathogen as well as its urease activity and its binding to the HT29-MTX cell line decreased in a dose-dependent manner.…”
mentioning
confidence: 84%
“…Supported by an ever increasing catalog of fluorescent probes enabling multi-parametric assessment of bacterial physiology, FC allows us to assess the impact of antimicrobials on the bacterial host in real-time at both population and single-cell level. Studies using FC to investigate the impact of bacteriocins on the cells have generally utilized a combination of probes enabling the assessment of changes in membrane integrity (e.g., Syto 9 and PI), membrane potential [e.g., DiBAC 4 (3), DiOC 2 (3)] and intracellular metabolic activity (e.g., cFDA) (Ratinaud and Revidon, 1996; Ueckert et al, 1997, 1998; Swarts et al, 1998; Martínez et al, 2000; Shapiro, 2000; Budde and Rasch, 2001; Dalmau et al, 2002; Weeks et al, 2006; Gou et al, 2010; Ayari et al, 2012; Pal and Srivastava, 2014; Chopra et al, 2015). The ability to study individual cellular events and to distinguish them from the overall population response makes FC one of the most appropriate tools to provide real-time information regarding the potentially heterogeneous response of a bacterial population to a bacteriocin.…”
Section: Introductionmentioning
confidence: 99%
“…These observations were corroborated by transmission electron microscopy which clearly showed that the cell lysis had occured after treatment with the antimicrobial substance. The effect of the antimicrobial substance depends on the conditions of the experiment, like the dose and degree of purity of the bacteriocin, the indicator strain and its cellular concentration [30]. In this regard bacteriostatic may become a bacteriolytic effect by simply increasing the bacteriocin dose [24].…”
Section: Discussionmentioning
confidence: 99%